Gigantes brasileiros: multinacionais emergentes e competição global - Pinho, Ricardo Reisen (2008)
The purpose of this paper is to analyze how Brazilian companies have internationalized, and whether factors such as entrepreneurship and innovation resulted in effect change in their strategic orientation and operation so as to allow for a sustainable international expansion. An empirical research has been made in four organization chosen for their size, industry, stage of internationalization and organization structure. Although this research is an exploratory study which focuses on an ongoing process, it does point to some relevant evidence. The main conclusion is that there is an international expansion process in progress involving Brazilian firms, which is independent of size and industry the company operates in. However, it is still recent and meager when compared with the ones observed countries, or even with some other emerging countries. Secondly, most of these movements are by and large a consequence of the firms' own internal decision. Governmental policies are poor in pushing them in this direction, so far. In addition, although the analyzed Brazilian firms are yet in different stages of internalization, we could infer that both economic and behavioral theories explain in a complementary manner their strategic decision and stage of development. Finally, we perceived that factors such as entrepreneurship and innovation have had an important role in the decision of if and how to go international. Based on such investigation, this study suggest a guideline for future research.